Deceptive Strategies in Literature: The Meaning of Folded Story - Silvia Rosa (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
Tambo Minangkabau is a storehouse of knowledge about the history of the Minangkabau people. Initially, it developed as oral literature, passed from generation to generation in the Minangkabau community in West Sumatra, an Indonesian provinces with a matrilineal kinship structure. However, after the Minangkabau people embraced Islam, Tambo began to be written using Jawi characters in Arabic thus becoming an historical literary work. Tambo tells the history of the Minangkabau ethnic group and also the history of customs and Minangkabau culture. Tambo records past events, stories about the origins of Minangkabau ancestors, philosophy, norms and laws in community life, and even the tragedies that have occurred in this ethnic group. To express the tragedies that have occurred in the past history of the Minangkabau ethnic group, Tambo uses the power of symbolic language. There are two episodes in Tambo that illustrate this. This article reveals the strategy of hiding a tragedy by the Minangkabau tribe through the power of the use of language in historical literary works, especially those depicted in the episodes of “Teka-teki Kayu Tataran” and “Teka-teki Unggas”.